Zmiany położenia prawnego handlu prywatnego w latach 1946–1947 : Przechodzenie od modelu trójsektorowego do upaństwowienia - Horubski, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article addresses the dynamic changes in the legal situation of private trade in the People’s Poland period between 1946 and 1947. In the indicated period, there was a departure from the previously proclaimed three-sector model of organization of commercial activity. This model involved the co-existence of state, cooperative and private trade. In 1947, as part of the so-called “battle for trade”, a series of regulations was issued to rapidly reduce the extent of private trade. The study focuses on the commercial enterprise permits introduced at that time as an instrument for liquidating the private commercial sector. The obligation to obtain such permits concerned not only new commercial ventures, but also limited the right to continue previously conducted activities. The actions of the authorities of the People’s Poland presented in the article led to the disappearance of the private commercial sector, thus opening the way to the domination of state trade.
Keywords: handel; kupcy; reglamentacja działalności gospodarczej; zezwolenia; trójsektorowy model organizacji handlu; upaństwowienie